Analisis Kepuasan Konsumen Air Minum Isi Ulang Depot Sikumbang Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru - Dehanindah, Ismi; Nurwati, Niken; Harmadi, Desma (Jurnal Agribisnis, 2024)
The role of refillable drinking water is getting bigger, this can be seen by the increasing amount of refillable drinking water everywhere. So the competition among refillable drinking water companies is getting sharper. The customer satisfaction strategy causes competitors to have to work hard and do high costs in an effort to win over the consumers of a company. The purpose of this study is to analyze the influence of product quality, service quality and price on consumer satisfaction of refillable drinking water at Sikumbang Depot, Maharatu Village, Marpoyan Damai District, Pekanbaru City. The time used in this study starts from February to April 2024. The sampling technique in this study was Purposive sampling, the number of respondents taken was 75 respondents. The method that can be used in this study is to use multiple linear regression analysis using the SPSS For Windows software program version 23. The results of this study showed that there was an influence of service quality on consumer satisfaction with a regression result of 0.134 and a t-count value of 4.343 > a t-table value of 1.667. There was an effect between price on consumer satisfaction with a regression result of 0.248 A t-calculated value of 6.492 > a t-table value of 1.667 and No effect between product quality on consumer satisfaction with a regression result of -0.015 and a t-calculated value of -0.494 < a t-table value of 1.667.